The Relationship between Retirement Problems and Psychological Flexibility among Palestinian Retirees in Gaza Governorates (Journal Of Educational and Psychological Researches, 2015)
The study aims at knowing the relationship between retirement problems and psychological flexibility, besides identifying the difference of retirement problems and psychological flexibility due to the wok place variable and sex variable.The study sample consists of 250 registered retirees in both associations of the government and the UNRWA. The researcher had prepared and used a retirement problems scale and  a psychological flexibility scale. The study findings show the following:• The economic problems were greatly common by a relative weight of 76.3 %. • The psychological compatibility was the most widespread domain in the psychological flexibility scale among the retirees by a relative weight of 56.33%.• A negative relation was recorded between retirement problems and psychological flexibility among the retirees. • There were no statistically significant differences in all domains of the retirement problems scale and the total score due to the work place variable, except for the economic problems that were in favor of the UNRWA retirees. • There were no statistically significant differences in all domains of the psychological flexibility scale and the total score. • There were statistically significant differences in all domains of retirement problems due to sex variable in favor of males, while  no statistically significant  differences in  psychological flexibility due to sex variable.